Acute and sub-acute toxicity study of aqueous and methanol root extract of Tetracera alnifolia in male albino rats - Irene Ebosereme Ainyanbhor; Iyere Osolase Onoagbe; Great Iruoghene Edo; Emad Yousif; Patrick Othuke Akpoghelie; Joseph Oghenewogaga Owheruo; Endurance Fegor Isoje; Ufuoma Augustina Igbuku; Arthur Efeoghene Athan Essaghah; Huzaifa Umar (Toxicology Reports, 2024)
The aim of this study was to assess the acute and sub-acute toxicity of aqueous and methanol extracts of the root of Tetracera alnifolia as well as the effects on some biochemical parameters in albino rats as many plants used in traditional medicine lack scientific and clinical evidence to support a better understanding of their safety and efficacy. Phytochemical screening and proximate analysis of the pulverised root of Tetracera alnifolia was carried out using previously reported protocol. Sub-acute toxicity study of each extract was done for 28 days followed by organs function tests and histopathology studies of the liver, kidney and heart. Evaluation of lipid profile and oxidative stress marker to ascertain the effect of each extract on lipid peroxidation and their antioxidant property was done after administration of 200 mg/Kg body weight of each extract for a period of thirty-five days. Acute toxicity study of each extract gave oral LD50 (rat) of greater than 5000 mg/kg body weight with no signs of toxicity. Sub-acute toxicity study showed both extracts were non-toxic to the liver, kidney, heart and blood at doses between 200 and 3000 mg/Kg body weight assessed by the respective organ function tests, hematological parameters, and histopathology study. However, higher doses seem toxic to the liver particularly at 5000 mg/kg B. W due to increase in plasma AST, ALT and ALP activities accompanied with reduced protein and albumin concentrations. Effects of each extracts at 200 mg/Kg body weight on some biochemical parameters revealed no significant difference in lipid profile parameters and no lipid peroxidation. Each extract may possess antioxidant property due to increase in catalase activity. The result from this research may help validate the safety of the oral use of this plant in traditional medicine.